2021
DOI: 10.4314/jpb.v18i2.8
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility and molecular characterization of mec A- and mec B-positive community acquired methicillin-resistant Staphylococcus aureus isolates from students

Abstract: Staphylococcus aureus is an organism of great public health importance. It is widely studied because it is virulent, causes life threatening disease and has ability to adapt to diverse environmental conditions and so develops resistance to antibiotics easily. As a result, there is a need for surveillance of its antibiotic resistance and resistance genes. The susceptibility and molecular characterization of methicillin resistant Staphylococcus aureus recovered from urine samples of healthy students were underta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…Thus, the possibility of a different MRS mechanism in the study area is highly probable which needs further investigation. Some studies that have explored further mecA and mecC negative isolates have identified the presence of the mecB homologue, hyperproduction of β-lactamase, and production of modified PBPs [17,[107][108][109]. Further, class 1 and 2 integrons containing dfrA12-orfF-aadA2, dfrA17-aadA5, aadA2, and aadB, oxa2, aacA4, orfD-aacA4-catB8, aadB-catB3, orfD-aacA4 and aadB-aadA1-cmlA6, dhfrA1-sat2-aadA1, dhfrA11, dhfrA1-sat2 gene cassettes, respectively, have been detected in resistant Staphylococcus isolates in the past [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the possibility of a different MRS mechanism in the study area is highly probable which needs further investigation. Some studies that have explored further mecA and mecC negative isolates have identified the presence of the mecB homologue, hyperproduction of β-lactamase, and production of modified PBPs [17,[107][108][109]. Further, class 1 and 2 integrons containing dfrA12-orfF-aadA2, dfrA17-aadA5, aadA2, and aadB, oxa2, aacA4, orfD-aacA4-catB8, aadB-catB3, orfD-aacA4 and aadB-aadA1-cmlA6, dhfrA1-sat2-aadA1, dhfrA11, dhfrA1-sat2 gene cassettes, respectively, have been detected in resistant Staphylococcus isolates in the past [32][33][34].…”
Section: Discussionmentioning
confidence: 99%